Analysis of key factors and prediction of gas production pressure of coalbed methane well: Combining grey relational with principal component regression analysis. Issue 4 (July 2019) - Wu, Caifang; Liu, Xiaolei; Zhou, Qizhong; Zhang, Xiaoyang
The critical desorption pressure is different from the gas production pressure of coalbed methane. Gas production pressure is affected by many factors, but their relationships are not obvious. Therefore, it is difficult to predict gas production pressure accurately. To address this problem, the effect of physical properties of coal reservoir upon gas production pressure of coalbed methane well was evaluated by grey relational analysis. The parameters of the physical properties of coal reservoir were classified into three types: energy parameters, migration channel parameters and characteristic parameters of adsorption and desorption. According to the results of the grey relational analysis, the major controlling factors were selected, and the principal component regression analysis was carried out. Furthermore, the gas production pressure of coalbed methane well was predicted accurately based on the regression model. The results of grey relational analysis and principal component analysis revealed that the energy of coal reservoir providing the power for coalbed methane migration is the fundamental role. The migration channel that decides the extent of reservoir energy loss is the key factor. Characteristics of adsorption and desorption, which affect the reservoir energy and the development degree of the migration channel, are necessary.